MARKET SHARE AND CUSTOMER EQUITY MEASUREMENT USING MARKOV CHAIN - Asnan Furinto; Yaya Heryadi; Tri Asih Budiono (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
Various techniques have been developed to measure firm's market share and the return on investment (ROI) of firm's marketing expenditures. However, most of those techniques are usually used to assess the past performance of a marketing program, using history of longitudinal data instead of expected future performance of a planned marketing program. In the absence of historical data base, measurements of expected ROI could still be carried out using a cross sectional survey, evaluating customer future purchase intentions as influenced by a new loyalty program to be launched by the firm in near future. Using survey of domestic airline passengers and Markov Chain approach, the model incorporates competition whereby customers are free to switch from one carrier to another from time to time. Expected ROI of loyalty program is measured by changes in the customer equity. Using MatLab software, future market share of Lion Air, Mandala Air, and Merpati Airline could be estimated quite accurately, and subsequently, changes in customer equity could be measured. Loyalty programs indeed induce changes in customers' future share of wallet and customer equity. Managers are encouraged to regularly conduct customer survey to guide them prior to launching a marketing action, using changes in customer equity as the ultimate dependent variable of ROI measurement.